2020
DOI: 10.1097/mnm.0000000000001353
|View full text |Cite
|
Sign up to set email alerts
|

Two-bed SPECT/CT versus planar bone scintigraphy: prospective comparison of reproducibility and diagnostic performance

Abstract: Objective To evaluate the reproducibility and diagnostic performance of two-bed single-photon emission computed tomography/computed tomography (SPECT/CT) images (TBSCT), compared to conventional planar bone scintigraphy (PBS) for the diagnosis of osseous metastasis. Methods Patients with known solid tumor, referred to perform PBS, were included in this prospective study. PBS acquisition was followed by TBSCT images, covering at least the chest, abdomen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…Similar results were achieved by other studies [2,7–11] that showed significant improvement in inter-observer variability for SPECT/CT (whatever the technique used) compared to planar BS or SPECT alone, with a kappa value ranging from 0.78 to 91 for SPECT/CT. Beck et al .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were achieved by other studies [2,7–11] that showed significant improvement in inter-observer variability for SPECT/CT (whatever the technique used) compared to planar BS or SPECT alone, with a kappa value ranging from 0.78 to 91 for SPECT/CT. Beck et al .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that the inter-observer agreement between readers significantly improved by addition of SPECT/CT to Planar BS from fair 0.372 to perfect agreement 0.847. Similar results were achieved by other studies [2,[7][8][9][10][11] that showed significant improvement in inter-observer variability for SPECT/CT (whatever the technique used) compared to planar BS or SPECT alone, with a kappa value ranging from 0.78 to 91 for SPECT/CT. Beck et al [9].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The diagnostic performance of the 20 min and 3 min DL SPECT/CT images was not significantly different according to both reviewers in our study. These results are similar to those reported in traditional SPECT/CT bone scans studies (Zhang et al 2020, Mostafa et al 2021. Although the sensitivity of the 3 min DL SPECT/CT images was 10% lower than that of the 20 min images, this different was not statistically significant and would be considered acceptable in clinical practice.…”
Section: Discussionsupporting
confidence: 88%